Developing holistic leadership : a source of business innovation - Kodama, Mitsuru, 1957- (Emerald Publishing Limited, 2017)
The book intends to make a contribution to new theoretical concepts and knowledge to existing leadership theory. Through in-depth case studies of international corporations that have achieved business innovation, the book aims to provide new leadership theory of practitioners who promote strategic knowledge creation activities to achieve business innovation and new practical insights. The book discusses in detail theoretical concepts and practical knowledge in the leadership interaction among the different management layers (top, middle and lower layers) and among the different layers (formal layer, psychological boundary layer, and informal layer).